Response of cumin (Cuminum cyminum L.) to ’panchgavya’ and plant leaf extracts in arid western Rajasthan - R S Mertia, R N Kumawat, S S Mahajan (Journal of Spices and Aromatic Crops, 2009)
A field experiment was conducted at Jaisalmer (Rajasthan) to study the effect of foliar appliedneem (Azadirachta indica), datura (Datura metel) and tumba (Citrullus colocynthis) leaf extractsin 1:1 combination with ’panchgavya’ on growth and yield of cumin (Cuminum cyminum).The results revealed that synthesis of chlorophyll and activity of nitrate reductase in freshleaves increased significantly with application of neem + panchgavya compared to control at55 and 80 days after sowing. Dry matter accumulation, branches plant-1, umbels plant-1,seeds umbel-1 and 100-seed weight also recorded significant increase with application of neem+ ’panchgavya’. Compared to control, neem + ’panchgavya’ increased grain, straw andbiological yield by 58%, 72% and 65%, respectively. The content and uptake of N and P inseed and straw also recorded significant increase with application of neem + ’panchgavya’.Application of foliar sources both at branching and flowering stages recorded significantlyhigher accumulation of dry matter, yield and yield attributes, content and uptake of N and Pin seed and straw compared to single application at branching or flowering.